2022
DOI: 10.3389/fendo.2022.855197
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate lymphoid Cells in Obesity and Insulin Resistance

Abstract: Obesity, a growing chronic metabolic disease, greatly increases the risk of metabolic syndrome which includes type 2 diabetes, fatty liver and cardiovascular diseases. Obesity-associated metabolic diseases significantly contribute to mortality and reduce life expectancy. Recently, innate lymphoid cells (ILCs) have emerged as crucial regulators of metabolic homeostasis and tissue inflammation. This review focuses on the roles of ILCs in different metabolic tissues, including adipose tissue, liver, pancreas, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 197 publications
0
5
0
Order By: Relevance
“…Moreover, recent studies also found that ILC1s in the adipose tissue participate in developing inflammation and insulin resistance. HFD-induced obesity increases the number of ILC1s and induces them to produce IFN-γ and TNFα in the visceral adipose tissue (VAT), then ILC1s-derived IFN-γ and TNFα accelerate M1 macrophages accumulation and promote insulin resistance [211].…”
Section: Other Immune Cells and Insulin Resistancementioning
confidence: 99%
“…Moreover, recent studies also found that ILC1s in the adipose tissue participate in developing inflammation and insulin resistance. HFD-induced obesity increases the number of ILC1s and induces them to produce IFN-γ and TNFα in the visceral adipose tissue (VAT), then ILC1s-derived IFN-γ and TNFα accelerate M1 macrophages accumulation and promote insulin resistance [211].…”
Section: Other Immune Cells and Insulin Resistancementioning
confidence: 99%
“…The findings suggested that COS may prevent diet-induced weight gain and that the antiobesity effect is mediated partially via inhibiting adipogenesis and increasing adiponectin levels [ 77 ]. Obesity, the most common chronic metabolic disease, has been proved to induce low-grade inflammation [ 78 ]. The studies above supported the feasibility that COS with anti-inflammatory activity can be applied as a nutraceutical against metabolic diseases such as diabetes and obesity.…”
Section: Biological Activities Of Chitosan and Cosmentioning
confidence: 99%
“…Particularly, a major role has been attributed to intestinal ILC2s and, to a much lesser extent, to ILC3s, while ILC1s seem to play a more relevant role in adipose tissue. ILC1s participate in the induction of inflammation and development of insulin resistance [22]. Here, the significant reduction in hepatic total lipids in the animals fed with the LMWF is unlikely to suggest the expansion of pluripotential CD117 + cells towards a cytotoxic/proinflammatory ILC1s-like phenotype.…”
Section: Discussionmentioning
confidence: 79%